Ensinando probabilidade com o jogo de dados de Mozart - Boni, Djones Aldivo (2021)
The present work’s objective is to elaborate a proposal to teach probabilities, based on Mozart’s Dice Game. The research presents itself with an exploratory-descriptive characteristic, developing a proposal that uses group activities with targeted discussions, so that students raise hypotheses, discuss methods to test them and, thereby, solve the suggested problems. Within the proposal are adressed: concepts of combinatorics, probabilities, probability distributions and the use of experimentation to test probabilistic hypotheses. Additional content was prepared as a supplement to the proposal: an educational product (in the form of a website), teaching materials and a selection of technological resources available on the internet. In addition, it was carried out a field research, applying the teaching proposal with high school and first undergraduate students, followed by an evaluation questionnaire. For this, the proposal was adapted to the format of a videoconference and it was applied to high school students, as well as a supplementary application with a video class with high school and first undergraduate students. The questionnaire applied to students sought to identify the target audience, ascertain aspects of interest and identify learning attributes about them. In the evaluation of the responses to the questionnaire the following impressions were identified: positive reaction of the students, interest in the subject and learning of the content, which positively may have been influenced by personal motivations of the students, such as liking music, playing musical instruments or enjoying math.